The Implementation Of Restorative Justice Policy For Narcotics Abuse Crime - Ersya Ananda Kusuma Wardani; Muhammad Rustamaji (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
Narcotics Abuse has become a vital problem in several countries, including Indonesia. To solve the problem, the Indonesian government has implemented various policies, including a restorative justice policy. The regulation highlighted rehabilitation, reconciliation, and reintegration for the perpetrators, victims, and community. This research aimed to evaluate the implementation of restorative justice regulation in the treatment of drug abuse in Indonesia. The descriptive qualitative method in this study was done through the analysis of literature reviews from various sources related to the application of restorative justice policy for narcotics abuse. The results showed that the implementation of restorative justice policy still got some challenges, even though the regulation was directly adopted to handle narcotics abuse. The contributed factors were the lack of understanding about narcotics abuse and society support, limited resources, and the disagreement among agencies and those factors influenced the effectiveness of the policy implementation. In conclusion, the implementation of restorative justice policy needs more attention and progress continuity, even though the policy has offered an approach that has effective potential in treating narcotics abuse. It needs great attempt to make the society understand the problem, better communication among the agencies, and the allocation of enough resources to effectively support the policy.